Cognitive aging and hearing acuity: modeling spoken language comprehension - Wingfield, Arthur; Amichetti, Nicole M.; Lash, Amanda (Frontiers in Psychology, 2015)
The comprehension of spoken language has been characterized by a number of “local” theories that have focused on specific aspects of the task: models of word recognition, models of selective attention, accounts of thematic role assignment at the sentence level, and so forth. The Ease of Language Understanding (ELU) model (Rönnberg et al., 2013) stands as one of the few attempts to offer a fully encompassing framework for language understanding. In this paper we examine aspects of the ELU model that apply especially to spoken language comprehension in adult aging, where speed of processing, working memory capacity, and hearing acuity are often compromised. We discuss, in relation to the ELU model, conceptions of working memory and its capacity limitations, the use of linguistic context to aid in speech recognition and the importance of inhibitory control, and language comprehension at the sentence level. Throughout our discussion our goal is to offer a constructive look at the ELU model; where it is strong and where there are gaps to be filled.